Formation of publicly supported climate in Russia, conducive to сompliance with the rules and norms of moral-ethic code of moral behavior of preschool and school age children ............................. - R. V. Gavva (Вестник университета)
Currently in Russia there is an acute problem of actualization and updating the methods and ways of state-supported public education of children, which would hinder outbreaks of negative, immoral deviant behavior of children in the family, on the street, in schools, social groups. In this article, an analysis of the individual forms of upbringing, maintenance and stimulation of constructive and rational behavior of children and adolescents in the conditions of modem reality, presenting severe challenges has been given.